A Correlational Study Between Vocabulary Mastery and Speaking Ability of Senior High School Students - Rahma Setyaning Eka Putri; Zakiyah Tasnim; Bambang Arya Wija Putra (Departement of Mathematics Education, 2024)
The purpose of this research was to find out the correlation between the students' vocabulary mastery and the speaking ability of the tenth grade students of State Senior High School in Jember. This research was a quantitative research. It used correlational technique design. The sample of the research consisted of 32 students of tenth grade who were selected by using cluster random sampling technique. The instruments that were used in the research were a vocabulary test and a speaking test. The vocabulary test consisted of 40 multiple-choice questions. The speaking test was in the form of telling a story from a picture and recommending a place to visit. The data had been collected were analysed by using Pearson Product Moment Correlation. Based on analysing the data, it was found that students' vocabulary mastery and speaking ability were moderate correlation. Furthermore, there was a strong correlation between students' vocabulary mastery and speaking ability. This was shown by the value of r = 0.562.